Dusha Peterburga . Dusha Peterburga . Soul of Saint-Petersburg . Душа Петербурга - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Reminiscing about St. Petersburg. Featured in the program: Kamendrovskaia, Tat'iana (Journalist); Maksi, Diana (U.S. Consul in St. Petersburg on Culture and Press) Воспоминания о Санкт-Петербурге. В программе участвуют: Камендровская, Татьяна (Журналистка); Макси, Диана (Консул по вопросам культуры и печати Генерального консульства США в Петербурге)